Implementasi Peraturan Walikota Palembang Nomor 69 Tahun 2012 Tentang Pedoman Pemberian Hibah Dan Bantuan Sosial di Badan Pengelolaan Keuangan dan Aset Daerah Kota Palembang - Reni Apriani (Universitas Islam Negeri Raden Fatah Palembang, 2018)
The study is based on the problems caused by its implementation such as grant, as in grant management that is not in accordance with the provisions. Grants are granted with the aim of supporting the improvement of governance and development functions. Grant spending is included in one part of the revenue and expenditure area. In overcoming this matter, the Government of Palembang City has made the Regulation of Mayor of Palembang Number 69 Year 2012 on Guidance of Grant and Social Assistance in Regional Financial Management and Asset of Palembang City. In this case the authors narrow the research that is on grant expenditure. In the Mayor Regulation there are rules in the process of grant giving for maximum results. This research is intended to find out how the grant in Palembang City Government. This study uses qualitative research methods with the four dimensions that are in the focus of research is the level of compliance, Smooth routine functions, performance and impacts arising from the policy. Based on the result of the research, it can be concluded that the Implementation of the Mayor of Palembang Regulation Number 69 of 2012 on the Guidance Grant and Social Assistance this particular grant has not been successful.